BEDAWANG NALA: ARTISTIC INSPIRATION FOR A FICTION FILM TO STRENGTHEN ENVIRONMENTAL EDUCATION AWARENESS - Putra, Ida Bagus Hari Kayana; Peradantha, Ida Bagus Gede Surya; Widyastuti, Ida Ayu Gede Sasrani (Institut Seni Indonesia Denpasar, 2024)
This research explores the philosophical and symbolic value of Bedawang Nala in Balinese architectural art and the development of its narrative in fiction films based on Hindu mythology. Bedawang Nala, depicted as a giant fire-haired turtle with dragons Anantabhoga and Basuki, reflects cosmic balance and natural harmony in Tri Hita Karana. This qualitative research uses an interdisciplinary perspective involving the views of cultural studies and the creativity of film art creation. Data was obtained through in-depth interviews to explore the meaning and connection of the Bedawang Nala concept with environmental themes, audiovisual observations of traditional Balinese architecture, and literature studies on Bedawang Nala and ecological issues. Data were analyzed using interview transcript interpretation techniques to identify main themes related to the philosophical and symbolic values of Bedawang Nala, audiovisual analysis, and literature synthesis that connects findings from interviews and observations with current discussions about ecological education. The findings show that the Bedawang Nala mythology is not just an aesthetic ornament but has an educational value relevant to contemporary environmental issues. The development of this mythology-based film narrative can be an effective academic and cultural reflection tool, strengthening ecological awareness in society. This research suggests making and evaluating films based on Bedawang Nala and exploring other local mythologies to increase the educational impact and environmental awareness through film media.